2013
DOI: 10.5539/jgg.v5n2p55
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contaminated Water, Soils and Crops in Peri Urban Wastewater Irrigation Farming in Mufulira and Kafue Towns in Zambia

Abstract: Although research on peri urban arable farming had been conducted in Zambia, the concerns related to heavy metal contaminated wastewater use in crop farming in peri urban areas were inadequately tackled. The study investigated heavy metal contamination of water, soils and crops at two study sites in Zambia. The two study sites were New Farm Extension in Mufulira and Chilumba Gardens in Kafue. Heavy metals comprising chromium (Cr), cobalt (Co), copper (Cu), lead (Pb) and nickel (Ni) were investigated due to: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…However, heavy metals possess undesirable and harmful consequences on food chains and human health (Huang et al., ; Sarfo et al., ; Zhang, Cui, Sheng, & Wang, ). Thus, studying the distribution of heavy metals in soil and lake sediments is beneficial in providing valuable information and insights about their contamination and potential environmental risks (Kapungwe, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, heavy metals possess undesirable and harmful consequences on food chains and human health (Huang et al., ; Sarfo et al., ; Zhang, Cui, Sheng, & Wang, ). Thus, studying the distribution of heavy metals in soil and lake sediments is beneficial in providing valuable information and insights about their contamination and potential environmental risks (Kapungwe, ).…”
Section: Introductionmentioning
confidence: 99%
“…It experiences tropical savannah climate characterised by three typical seasons; hot and wet season from November to March; cool and dry season from April to July and; hot and dry season from August to October (Kapungwe 2013). The town is located in the high rainfall agro-ecological region which is part of the Central African Plateau.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…The minimum and maximum temperatures during the same period were 12 and 29 ˚C respectively (Zambia Meteorological Department, 2015). The high rainfall has resulted in highly leached, and consequently highly acidic sandy soils (Mutamba, 2007).The district is characterized by a crop growing period of 190 days (Kapungwe, 2013). …”
Section: Description Of Study Areamentioning
confidence: 99%
“…The South and Southeast Asian countries, like Peninsular Malaysia, Vietnam, India, Thailand, Philippines, Indonesia, Bangladesh and Pakistan have taken much care regarding monitoring of the contamination of agricultural soils and crops by heavy metals. Kapungwe (2013) has studied metal (Co, Cr, Cu, Pb and Ni) contamination of water, soils and crops at two wastewater-irrigated study sites (New Farm Extension in Mufulira and Chilumba Gardens in Kafue) in Zambia. The results indicated that heavy metals were present in the water, soil and crops at the two study sites and exceeded acceptable limits.…”
Section: Introductionmentioning
confidence: 99%